Rebranding of Poso Regency Tourism After Social Conflict - Andi Akifah; Rizqy Alfiyaty; Nabillah Sasha Monica (BPSDMP Kominfo Manado, 2021)
After the social conflict with the issue of ethnicity, religion, race and inter-group. the image of Poso Regency has changed to become a